2018
DOI: 10.1111/jnc.14281
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of neuroprotection against ischemic insult by stress‐inducible phosphoprotein‐1/prion protein complex

Abstract: Stress-inducible phosphoprotein 1 (STI1) acts as a neuroprotective factor in the ischemic brain and its levels are increased following ischemia. Previous work has suggested that some of these STI1 actions in a stroke model depend on the recruitment of bone marrow-derived stem cells to improve outcomes after ischemic insult. However, STI1 can directly increase neuroprotective signaling in neurons by engaging with the cellular prion protein (PrP ) and activating α7 nicotinic acetylcholine receptors (α7nAChR). Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…Using the hypoxia-ischemia brain damage model in neonatal rats, it was shown that pathological changes in the brain are significantly reduced by an intraperitoneal injection of activin A, confirming that the application of activin A reduces brain tissue damage induced by hypoxia-ischemia (An et al, 2005 ). In addition, in the OGD/reperfusion model in primary neuronal cultures, researchers used neuroprotector stress-induced phosphoprotein 1 (STI1) to treat neurons and found that STI1 is dependent on activin-A receptor 1 (ALK2) for the inhibition of neuronal apoptosis (Beraldo et al, 2018 ). Thus, since ALK2 acts as a downstream mediator of the STI1 neuroprotection pathway, it may be useful as a therapeutic target for ischemic brain injury (Beraldo et al, 2018 ).…”
Section: Treatment Of Brain Injury Targeted To Activin Amentioning
confidence: 99%
See 1 more Smart Citation
“…Using the hypoxia-ischemia brain damage model in neonatal rats, it was shown that pathological changes in the brain are significantly reduced by an intraperitoneal injection of activin A, confirming that the application of activin A reduces brain tissue damage induced by hypoxia-ischemia (An et al, 2005 ). In addition, in the OGD/reperfusion model in primary neuronal cultures, researchers used neuroprotector stress-induced phosphoprotein 1 (STI1) to treat neurons and found that STI1 is dependent on activin-A receptor 1 (ALK2) for the inhibition of neuronal apoptosis (Beraldo et al, 2018 ). Thus, since ALK2 acts as a downstream mediator of the STI1 neuroprotection pathway, it may be useful as a therapeutic target for ischemic brain injury (Beraldo et al, 2018 ).…”
Section: Treatment Of Brain Injury Targeted To Activin Amentioning
confidence: 99%
“…In addition, in the OGD/reperfusion model in primary neuronal cultures, researchers used neuroprotector stress-induced phosphoprotein 1 (STI1) to treat neurons and found that STI1 is dependent on activin-A receptor 1 (ALK2) for the inhibition of neuronal apoptosis (Beraldo et al, 2018 ). Thus, since ALK2 acts as a downstream mediator of the STI1 neuroprotection pathway, it may be useful as a therapeutic target for ischemic brain injury (Beraldo et al, 2018 ). It was also shown that activin A reduces brain edema and the release of inflammatory cytokines in neonatal rats after hypoxic-ischemic brain damage and plays a role in nerve regeneration and functional repair, by increasing nestin protein expression, as well as the number and differentiation of neural stem cells (Peng et al, 2006 ; Zhang et al, 2016 ).…”
Section: Treatment Of Brain Injury Targeted To Activin Amentioning
confidence: 99%
“…the cell from apoptosis (Beraldo et al 2015). It would be of value to carry out further work to determine the effects of increased amine incorporation on the biochemical properties and functions of this and the other proteins identified as potential substrates of TG2 in OP-treated differentiating N2a cells.…”
Section: Discussionmentioning
confidence: 99%
“…Stip1, along with HSP 90-beta, stress-70 cognate 71 kDa and HSP 60 are chaperone proteins involved in cytoprotection, modulation of protein folding and transport, and have been shown to be up-regulated after a toxic insult by the OP nerve agent sarin in mouse brain (Chaubey et al 2017 ). The level of Stip1 also increased in the brain following ischaemia, inducing neuroprotective signals that rescue the cell from apoptosis (Beraldo et al 2015 ). It would be of value to carry out further work to determine the effects of increased amine incorporation on the biochemical properties and functions of this and the other proteins identified as potential substrates of TG2 in OP-treated differentiating N2a cells.…”
Section: Discussionmentioning
confidence: 99%
“…STI-1-PrPC interaction leading to a Ca2+ influx through α7nAchR is promoted by the physical interaction of the latter with PrPC [ 105 ]. Independently of PrPC, STI-1 can signal through other receptors (i.e., Activin receptor-Like Kinase-2 (ALK2) receptors), which can also have an important role in ischemic protection as shown for neurons subjected to OGD [ 106 ].…”
Section: An Overview Of Prp-associated Signaling Pathways and Theimentioning
confidence: 99%